Ferroptosis is a new therapeutic target for spinal cord injury - Bai, Xin-Yue; Liu, Xiao-Long; Deng, Zhi-Zhong; Wei, Dong-Min; Zhang, Die; Xi, Hui-Lin; Wang, Qing-Yan; He, Meng-Ze; Yang, Yan-Ling (Frontiers in Neuroscience, 2023)
Spinal cord injury is a serious traumatic disease. As Ferroptosis has been increasingly studied in recent years, it has been found to be closely related to the pathophysiological processes of spinal cord injury. Iron overload, reactive oxygen species accumulation, lipid peroxidation and glutamate accumulation associated with Ferroptosis are all present in spinal cord injury, and thus Ferroptosis is thought to be involved in the pathological processes secondary to spinal cord injury. This article highlights the relationship between Ferroptosis and spinal cord injury, lists substances that improve spinal cord injury by inhibiting Ferroptosis, and concludes with a discussion of the problems that may be encountered in the clinical translation of Ferroptosis inhibitors as a means of enabling their faster use in clinical treatment.